Decision-Making Process in Comprehensive Medication Management Services: From the Understanding to the Development of a Theoretical Model - Isabela Viana Oliveira; Yone de Almeida Nascimento; Djenane Ramalho-de-Oliveira (Pharmacy, 2020)
In Comprehensive medication management (CMM), the practitioner applies a decision-making method to assess patients’ pharmacotherapy in order to identify and solve drug therapy problems. Grounded theory was used to understand how pharmacists make clinical decisions when providing CMM service. Data collection included individual semi structured interviews with 11 pharmacists, observation of clinical case discussions and CMM consultations provided by the participating pharmacists. Two main categories emerged: 1. Understanding the rational method of decision-making: the foundation of the patient care process. 2. Balancing the care equation: the objective and the subjective, which includes a theoretical proposal explaining the pharmacists’ decision-making process and the factors that can modify this process. The pharmacotherapy knowledge should guide the anamnesis. Thus, the professional can evaluate the indication, effectiveness, safety and convenience of medications used by the patient. After exploring patients’ medication experiences, pharmacists can follow two courses of action: helping the patient overcome barriers to medication use; or matching the pharmacotherapy to the patient’s routine. Professional autonomy and absence of the patient at the time of the decision were some factors that influenced the pharmacist’s decision. Findings provide a broad understanding of pharmacists’ decision-making process during the care of patients using medications. It can be applied as a basis for educational interventions to train professionals on decision-making.